2014
DOI: 10.1371/journal.pone.0092356
|View full text |Cite
|
Sign up to set email alerts
|

Pou5f1/Oct4 Promotes Cell Survival via Direct Activation of mych Expression during Zebrafish Gastrulation

Abstract: Myc proteins control cell proliferation, cell cycle progression, and apoptosis, and play important roles in cancer as well in establishment of pluripotency. Here we investigated the control of myc gene expression by the Pou5f1/Oct4 pluripotency factor in the early zebrafish embryo. We analyzed the expression of all known zebrafish Myc family members, myca, mycb, mych, mycl1a, mycl1b, and mycn, by whole mount in situ hybridization during blastula and gastrula stages in wildtype and maternal plus zygotic pou5f1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 70 publications
3
12
0
Order By: Relevance
“…Studies have also shown that overexpression of c-MYC through P53 results inhibition of proliferation and increased apoptosis (25). OCT4 plays an important role in c-MYC expression (26). Our findings also showed that changes in the cell cycle in the U266 cells line were not significant, but there were significant changes in the RPMI8226 cells in the G1 phase and S phase.…”
Section: Discussionsupporting
confidence: 56%
“…Studies have also shown that overexpression of c-MYC through P53 results inhibition of proliferation and increased apoptosis (25). OCT4 plays an important role in c-MYC expression (26). Our findings also showed that changes in the cell cycle in the U266 cells line were not significant, but there were significant changes in the RPMI8226 cells in the G1 phase and S phase.…”
Section: Discussionsupporting
confidence: 56%
“…Previous reports have shown the physiological roles of OCT4 in the transcriptional regulation of MYC family members in various species. 24 26 OCT4 stimulates MYC transcription for cell proliferation in human and mouse ES cells 24 , 25 and activates myc transcription for cell survival during zebrafish gastrulation. 26 In the present study, we found the pathological significance of OCT4 for MYCN transcription in human neuroblastoma cells.…”
Section: Discussionmentioning
confidence: 99%
“…Nanog and Oct4/Pou5f3 synergize with the ventral specification pathway via BMP signaling and Vox (Peres-Camps et al, 2016; this study). Pou5f3 regulates cell survival by inhibiting p53 (tp53) and activating mych (Kotkamp et al, 2014). The decrease in cell survival, observed in both Nanog and Oct4/Pou5f3 mutants, could be caused by multiple independent changes due to a widespread role of Nanog and Pou5f3 in gene expression.…”
Section: Reduced Survival Of Mznanog Cells Is Independent Of Gastrulamentioning
confidence: 99%
“…We used a modified procedure from Kotkamp et al (2014). Embryos were fixed at 3, 4 and 4.7 hpf in Gard's FG fixative for 2 h and incubated overnight in PBST containing 0.33 M glycine.…”
Section: Estimating Of Mitotic Frequency In Fixed Embryosmentioning
confidence: 99%
See 1 more Smart Citation